The effectiveness of play method in ESL learning among preschoolers in Malaysia - Nair, Subadrah Madhawa; Yusoff, Sue Mohd; Hui, Lee Kar; Qing, Yeo Hui; Bokari, Umi Kalsum (Edelweiss Applied Science and Technology, 2025)
This research aims to explore the role of the play method in enhancing Malaysian preschoolers’ English learning in ESL classrooms. This study employed a quasi-experimental design, using both quantitative and qualitative data to determine the effectiveness of integrating the play method in teaching verbs among preschoolers. The sample consisted of 10 preschoolers (K2) aged 6 years, five teachers, and four parents to examine their perspectives on play-based learning. A pre-test, post-test, and semi-structured interview questions were used as instruments to collect data. The parents and teachers were interviewed by the researchers to examine their perspectives on play-based learning. Prior to the intervention, the preschoolers were given a pre-test to gauge their understanding of verbs. Following that, the children were taught verbs using the play method over three weeks. After the intervention, the children were given a post-test to ascertain the effectiveness of the play method in improving their scores in learning verbs. The results indicate that the play method enhanced preschoolers’ scores in mastery of verbs. In addition, the findings have valuable implications that may contribute to early childhood educators, parents, or caregivers on integrating the play method in ESL classrooms more effectively.